Social Intermodal Yonghegong 雍和宮: Highway-scraper - Loaíza Villagrán, Sebastián (Universidad de Chile. Facultad de Arquitectura y Urbanismo, 2016)
The Economic boom called for an explosion of car infrastructure in Beijing. This thesis explores the possibility to live and cohabit with large systems of vehicular infrastructures and wonders; what would we do if we had that space?